2017
DOI: 10.1590/s1677-5538.ibju.2016.0405
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of detrusor underactivity: a short term proof of concept study

Abstract: Objectives To compare the surgical outcomes of men with bladder outlet obstruction (BOO) due to benign prostatic obstruction (BPO) to those with detrusor underactivity (DU) or acontractile detrusor (DA).Materials and Methods This retrospective, IRB approved study included men who underwent BPO surgery for refractory LUTS or urinary retention. Patients were grouped based on videourodynamic (VUDS) findings: 1) men with BOO, 2) men with DU and 3) men with DA. The primary outcome measure was the Patient Global Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…Thomas et al [ 8 , 9 ] observed no long-term symptomatic nor urodynamic benefits from TURP in patients with impaired contractility without obstruction. In contrast, Blaivas and colleagues [ 10 ] reported that surgery afforded significant improvement in symptoms and bladder emptying in men with impaired contractility. Good outcomes have also been reported by Tanaka et al [ 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…Thomas et al [ 8 , 9 ] observed no long-term symptomatic nor urodynamic benefits from TURP in patients with impaired contractility without obstruction. In contrast, Blaivas and colleagues [ 10 ] reported that surgery afforded significant improvement in symptoms and bladder emptying in men with impaired contractility. Good outcomes have also been reported by Tanaka et al [ 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…Even in patients with DA, BOO surgery still provided improved treatment outcome for 58.8% of the DU patients. Recent studies have shown that patients with DU with or without BOO can still benefit from transurethral prostatic surgeries and have improvement of LUTS after surgery 18 , 19 . However, patients with DA might need CIC after prostatic surgery 19 , and patients with DU are more likely to have a lower quality of life and failure to voiding in the immediate postoperative period 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Data of a recent Cochrane and meta-analysis and of the RCT UPSTREAM study did not demonstrate the usefulness of preoperative urodynamics (UD) in these candidates to surgery [ 16 17 ]. However, several studies have shown that males with DUA, associated or not to BOO, had satisfactory results at short-time follow-up after surgery, but not long lasting-time [ 18 19 20 21 22 23 ]. Moreover, poorer surgical outcomes have been reported in underactive males than in non-underactive obstructed patients.…”
Section: Discussionmentioning
confidence: 99%